2012
DOI: 10.1097/ccm.0b013e31825b94d8
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of assessing symptoms in seriously ill intensive care unit patients

Abstract: Objectives Determine levels of agreement among intensive care unit patients and their family members, nurses, and physicians (proxies) regarding patients’ symptoms and compare levels of mean intensity (i.e., the magnitude of a symptom sensation) and distress (i.e., the degree of emotionality that a symptom engenders) of symptoms among patients and proxy reporters. Design Prospective study of proxy reporters of symptoms in seriously ill patients. Settings Two intensive care units in a tertiary medical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 58 publications
0
28
3
Order By: Relevance
“…Our results are in contrast to the findings in Puntillo et.al (32) who suggests that more experienced physicians reported symptom assessment closer to patient self-reports. This difference may be caused by that in the study by Puntillo et al most of the physicians were trainees, while in our study even the most naïve physician were residents with some years of ICU experience.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our results are in contrast to the findings in Puntillo et.al (32) who suggests that more experienced physicians reported symptom assessment closer to patient self-reports. This difference may be caused by that in the study by Puntillo et al most of the physicians were trainees, while in our study even the most naïve physician were residents with some years of ICU experience.…”
Section: Discussioncontrasting
confidence: 86%
“…The discrepancies between clinicians and patients appear to be even more apparent when symptoms are severe (30,31). Although Puntillo et al (32) found the average values of clinician ratings and patient ratings were nearly equal (in contrast to our present data), their ICC values show that clinicians did poorly at estimating an individual patient's shortness of breath (in agreement with our present data). In this study the assessments were completed within a range of 2-8 hours, while in our study the symptom ratings were done at the same time.…”
Section: Discussioncontrasting
confidence: 72%
“…In some studies, patients rank their symptoms higher than proxy reporters [33, 34], while in other reports the opposite is true [35, 36]. Recently, the agreement between ICU patients and their family members on the distress of patient pain, dyspnea, restlessness, fear, and thirst was demonstrated to be moderately strong [37]. Overall, data suggest that proxy reporters can help identify symptoms that might be distressing for the patient.…”
Section: What Are Key Elements Necessary To Assess Symptoms In the Icu?mentioning
confidence: 99%
“…Another study found that ICU nurses tended to overestimate symptom intensity and distress (Puntillo et al . ).…”
Section: Introductionmentioning
confidence: 97%